The Color Blue: A Comparative Exploration in English and Uzbek Languages (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article explores the significance and cultural implications of the color blue in both English and Uzbek languages. It examines how the color is perceived, represented, and utilized in various contexts, including literature, art, and everyday language. By comparing idiomatic expressions, cultural references, and emotional associations related to blue in both languages, the study highlights the similarities and differences in perceptions of color across cultures. The findings reveal how language shapes our understanding of color and its connotations, offering insights into broader cultural values and social norms.